2015
DOI: 10.1126/sciadv.1500157
|View full text |Cite
|
Sign up to set email alerts
|

Natural aerosols explain seasonal and spatial patterns of Southern Ocean cloud albedo

Abstract: Sulfate and organic mass in sea spray explain more than half of the variability in Southern Ocean cloud droplet concentration.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

22
237
0

Year Published

2015
2015
2018
2018

Publication Types

Select...
5
2

Relationship

4
3

Authors

Journals

citations
Cited by 195 publications
(270 citation statements)
references
References 92 publications
22
237
0
Order By: Relevance
“…Several studies have shown that sulfate mass concentration influences CDNC (Boucher and Lohmann, 1995;Lowenthal et 15 al., 2004;McCoy et al, 2017a;McCoy et al, 2015;Storelvmo et al, 2009). Previous studies relating sulfate mass to remotelysensed CDNC were hampered by significant retrieval bias, making the interpretation of their results difficult (McCoy et al, 2017a).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Several studies have shown that sulfate mass concentration influences CDNC (Boucher and Lohmann, 1995;Lowenthal et 15 al., 2004;McCoy et al, 2017a;McCoy et al, 2015;Storelvmo et al, 2009). Previous studies relating sulfate mass to remotelysensed CDNC were hampered by significant retrieval bias, making the interpretation of their results difficult (McCoy et al, 2017a).…”
Section: Discussionmentioning
confidence: 99%
“…For the analysis presented in this paper we adopt the technique used in previous studies (Gassó, 2008;Mace and Abernathy, 2016;Yuan et al, 2011;McCoy and Hartmann, 2015;McCoy et al, 2017b;Malavelle et al, 2017) and examine the response of cloud properties to volcanic sulfate sources. We support this analysis by examining the systematic change in 30 anthropogenic sulfur emissions from Asia and North America due to emissions controls , as in previous studies (Bennartz et al, 2011), although our data record extends over a period of enhanced emissions controls in East Asia and thus we anticipate a decrease in CDNC in contrast to Bennartz et al (2011).…”
Section: Decadal Trends In Cdnc Driven By Sulfur Fluxesmentioning
confidence: 99%
See 1 more Smart Citation
“…Around 3.4 Tg of sulfur is released to the atmosphere between December and February, a flux that represents ~15 % of global annual emissions of DMS (Jarníková and Tortell 2016). Elevated CCN numbers are seen in the most biologically active regions of the Southern Ocean, with a significant contribution from DMS-driven secondary aerosol formation processes (Korhonen 70 et al 2008;McCoy et al 2015). DMS-derived aerosols from this region are estimated to contribute 6 to 10 W m -2 to reflected short wavelength radiation, similar to the influence of anthropogenic aerosols in the polluted Northern Hemisphere (McCoy et al 2015).…”
mentioning
confidence: 99%
“…Elevated CCN numbers are seen in the most biologically active regions of the Southern Ocean, with a significant contribution from DMS-driven secondary aerosol formation processes (Korhonen 70 et al 2008;McCoy et al 2015). DMS-derived aerosols from this region are estimated to contribute 6 to 10 W m -2 to reflected short wavelength radiation, similar to the influence of anthropogenic aerosols in the polluted Northern Hemisphere (McCoy et al 2015). Given this important influence of polar DMS emissions on atmospheric processes and climate, it is vital we increase our understanding of the influence of future ocean acidification on DMS 75 production.…”
mentioning
confidence: 99%